Revealing the Impact of Ga and Y Doping on Thermal and Electrical Behavior of LaMnO3 Ceramic Materials - Paulina Vlazan; Catalin Nicolae Marin; Iosif Malaescu; Gabriela Vlase; Titus Vlase; Maria Poienar; Paula Sfirloaga (Applied Sciences, 2024)
The synthesis, thermal behavior and electrical properties of a series of undoped and 1% Ga- or Y-doped lanthanum manganite compounds, obtained via the sol–gel technique, are reported. Scanning electron microscopy (SEM/EDX), X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FT-IR) analyses were performed on all synthesized samples. The XRD results confirmed a good crystallinity for all studied samples, and a change in the crystal structure of Ga- or Y-doped lanthanum manganite (Pm-3m space group) was observed compared to the pristine sample (R-3c space group). Thermal analysis highlighted a different behavior of the doped samples compared to the undoped sample, observed by the different mass losses in the analyzed temperature range. For these materials, it is shown for the first time that the static electrical conductivity, σDC, of Ga- or Y-doped LaMnO3 compounds increases compared to the σDC of the pristine sample, and the thermal activation energy of the process of electrical conduction, EA,cond, increases linearly with the temperature for all three studied samples.